Thromboelastography in term neonates: an alternative approach to evaluating coagulopathy - Sewell, Elizabeth K; Forman, Katie R; Wong, Edward C C; Gallagher, Meanavy; Luban, Naomi L C; Massaro, An N (Archives of disease in childhood. Fetal and neonatal edition, 2017)
ObjectiveTo develop normative ranges for citrate-modified and heparinase-modified thromboelastography (TEG) in term neonates.DesignProspective observational study.SettingAn outborn neonatal and cardiac intensive care unit in a free-standing academic children's hospital.PatientsThirty term neonates were enrolled as control subjects. Seventeen infants with clinically documented bleeding requiring blood transfusion were enrolled in the comparison group.Main outcome measuresCitrate-modified and heparinase-modified TEG parameters were calculated from blood specimens drawn via peripheral arterial stick or arterial line.ResultsTEG in neonates differs from older children and adults; clotting time (R) and clot kinetics (K) values are generally lower while fibrinolysis or rate of clot breakdown (LY30) and coagulation index (CI) are often higher in neonates. TEG values in term neonates calculated as median (Q1–Q3) are as follows: R 4.150 (3.200–6.200), K 1.550 (1.200–1.800), α angle (α) 70.100 (66.000–72.900), maximum amplitude (MA) 61.850 (59.400–66.000), LY30 1.050 (0.100–1.600) and CI 1.950 (0.100 to 2.900). Cut points selected for optimal predictive value for bleeding using receiver operating curve analyses were R>6.3 (sensitivity 82.4%, specificity 80%); K>2.5 (sensitivity 82.4%, specificity 96.7%); α<59 (sensitivity 82.4%, specificity 96.7%); MA<57 (sensitivity 82.4%, specificity 86.7%); CI<−0.15 (sensitivity 88.2%, specificity 83.3%).ConclusionsThe reference ranges and cut points for citrate-modified and heparinase-modified TEG can be used to diagnose and evaluate coagulopathy in term neonates.